Comparative Study on Static and Dynamic Analyses of an Ultra-thin Double-Glazing PV Module Based on FEM. (August 2015) - Dong, Jinzhi; Yang, Hongxing; Lu, Xilin; Zhang, Hongmei; Peng, Jinqing
Abstract: This paper presents a numerical simulation work on the mechanical behaviors of an ultra-thin double-glazing PV module under static and dynamic load conditions. Three different kinds of PV mounting configurations are investigated respectively to explore their influences on the static and dynamic performance of the studied module. For each kind of mounting configuration, static, modal and modal-based steady-state dynamic analyses are carried out by using the Finite Element Method, respectively. In the static analysis, two kinds of uniform pressure loading conditions with magnitudes of 2400 Pa and 5400 Pa, which are standing for the maximum wind load and snow load respectively according to the Standard of IEC 61215, are applied on the PV modules. After static analyses, modal analyses are performed to obtain the PV modules' natural frequencies and mode shapes. Based on the results of modal analyses, a steady-state dynamic analysis is conducted to determine the modules' dynamic responses to the harmonic excitations with an amplitude of 2400 Pa and frequencies ranging from 0 Hz to 100 Hz. The simulation results show that both the deformation and the stresses of three PV system are small in static analysis, but they are quite different in dynamic analysis. The dynamic displacement curves have obvious oscillations near the natural frequencies of PV modules and the amplitudes are large enough to damage the PV modules. The mounting configurations have a significant influence on both the static performance (strength and deformation) and dynamic performance (dynamic characteristics and responses). In conclusion, for this ultra-thin double-glazing PV module, it is not accurate and appropriate for evaluating the safety and stability of the PV module just through the existing static analysis in IEC 61215. The dynamic effects of the loading on PV module also need to be paid attention. Moreover, the mounting configurations should be designed to meet both the static and dynamic requirements.